The Difficulties Facing Of The Mechanic Otomotif (Mo) Student At Smk Yapim Kabanjahe Using Participle In Sentences - Ersika Puspita Dani (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
Abstract. This study deals with the student’s difficulties in using participle in sentences. The purposes of the study were to find out whether or not the students found difficulties in using participle in sentence and to find out the type of difficulties they faced.The population of the study was the 2020/2021 of the Mechanic Otomotif (MO) students at SMK YAPIM Kabanjahe. In this sampling, all the population has equal chance to be selected for the sample. The total numbers of samples was 30 students. The instrument used to collect the data was multiple choice test. This research was conducted by applying the descriptive quantitative design. The reliability of the test is counted by using KR21 formula. The formula testing result showed that the reliability of the test was 0,89, it means that the test was very good. The finding showed that the students found some difficulties in using participle, they were : Present Participle (8,67 %), Past Participle (9,34 %) and Perfect Participle (9,33 %). Perfect Participle was regarded as the most difficult type for them, especially in using it after certain verbs and in replacing relative pronoun, and then followed Past Participle by especially in using in it replacing relative pronoun and after certain verb. And the last was Present Participle. The percentage of each difficulty was taken by dividing the wrong answer to the total correct answer of the test.